Commonwealth Caribbean: the integration experience - Chernick, Sidney E. (John Hopkins Univ. Pub. BaltimoreUS, 1978)
Highlights the problems and prospects of economic integration among small developing countries. Focuses on a group of twelve (British) Commonwealth Caribbean territories that are in the process of forging an integrated community.